Legal responsibility upon the negligence of entrepreneurs in registering their labors as the member of BPJS ketenagakerjaan - Sujana Donandi Sinuraya (University of Merdeka Malang, 2020)
Government have mandated the entrepreneurs to register their labors as the member of BPJS Ketenagakerjaan in accordance to the Law Number 24 Year 2011 regarding ‘Badan Penyelenggara Jaminan Sosial’ (BPJS)/ UU BPJS. In fact, Many labors are not registered. In Kabupaten Bekasi, 30 percents of the total labors are not registered. This research tries to examine the legal consequences upon the negligence of the entrepreneurs in Kabupaten Bekasi in registering their labors as the member of BPJS Ketenagakerjaan. This research also aims to examine the legal responsibility of the entrepreneurs in Kabupaten Bekasi towards their unregistered labors. The research methodology is Normative-Empirical Legal Research. The result shows that the legal consequences of the negligence of the entrepreneurs in Kabupaten Bekasi in registering their labor to BPJS Ketenagakerjaan is that the entrepreneurs could be punished with administrative sanction such as written reprimand, fine, and or prohibitation to access a certain public service. Meanwhile, legal responsibility of the entrepreneurs in Kabupaten Bekasi towards their labor appears in form of civil compensation. In case the dispute would be settled in Industrial Court, then the judges could sentenced the entrepreneurs to register their labor as the member of BPJS Ketenagakerjaan.How to cite item: Sinuraya, S. (2020). Legal responsibility upon the negligence of entrepreneurs in registering their labors as the member of BPJS ketenagakerjaan. Jurnal Cakrawala Hukum, 11(2), 222-230. doi:https://doi.org/10.26905/idjch.v11i2.4042